Precise Determination of the Angular Distribution of the Winding Inductance of a Switched Reluctance Motor - Fabiański, Bogdan; Pajchrowski, Tomasz; Zawirski, Krzysztof (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
The article describes a precise method to obtain the angular profile of the winding inductance of a switched reluctance motor. The introduction emphasises the importance of research carried out in the context of the development of fault-tolerant control of the motor drive. The basis of the analysis presented here is the study of the current waveform accompanied by a forcing voltage, thus revealing the finite dynamics of the circuit RL. The study considers the nonlinear approximation function modeling the current waveform against other simplified methods. Further data processing and the methodology used in the context of the proprietary hardware layer allow to obtain repeatable and reliable results.